PENGARUH LITERASI KEUANGAN, FINANCIAL SELF-EFFICACY, DAN LINGKUNGAN TEMAN SEBAYA TERHADAP MINAT BERINVESTASI MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS LAMPUNG - septiani putri; Pujiati Pujiati; Fanni Rahmawati; Albet Maydiantoro (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Students’ investment interest in the Economics Education Program of the Faculty of Teacher Training and Education at the University of Lampung is affected by various factors, including knowledge, psychological aspects, and the social environment. Low investment interest may hinder students in preparing long-term financial planning. This study aims to determine the effects of financial literacy, financial self-efficacy, and peer environment on the investment interest of Economics Education students at the University of Lampung. The study employed a quantitative approach using a descriptive-verificative method with ex post facto and survey designs. Data were collected through questionnaires distributed to 123 students selected using simple random sampling and were analyzed using multiple linear regression after meeting the requirements of instrument testing and statistical assumptions. The results indicate that financial literacy, financial self-efficacy, and peer environment simultaneously have a significant effect on students’ investment interest. These findings suggest that students with higher financial literacy, stronger financial self-efficacy, and a supportive peer environment tend to have greater investment interest. This study is limited to students of the Economics Education Program at the Faculty of Teacher Training and Education, University of Lampung; therefore, the findings may not be generalized to broader populations. The implications of this study highlight the importance of optimizing the role of academic programs in utilizing existing financial education facilities and activities, such as investment galleries and seminars, as well as fostering a positive academic social environment to enhance students’ investment interest.